Acetazolamide in Hypokalemic Periodic Paralysis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The mechanism of action of acetazolamide in the K-deficient diet rat, an animal model of human hypokalemic periodic paralysis (hypoPP), was investigated at the University of Bari, Italy.